2017
DOI: 10.2147/ijn.s148845
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of vascular endothelial growth factor-loaded silk fibroin to improve biological performance of ultra-high-molecular-weight polyethylene via promoting angiogenesis

Abstract: Ultra-high-molecular-weight polyethylene (UHMWPE) has been applied in orthopedics, as the materials of joint prosthesis, artificial ligaments, and sutures due to its advantages such as high tensile strength, good wear resistance, and chemical stability. However, postoperative osteolysis induced by UHMWPE wear particles and poor bone–implant healing interface due to scarcity of osseointegration is a significant problem and should be solved imperatively. In order to enhance its affinity to bone tissue, vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Direct insertion is composed of tendon, unmineralized fibrocartilage, mineralized fibrocartilage, and bone, while indirect insertion anchors the ligament to periosteum by Sharpey's fibers. 11 Li et al 29 and Ai et al 11 have reported IF between the graft and the host bone matured with narrowed width, fibrocartilage formation, and Sharpey's fiber formation at 12 weeks after ACL reconstruction, which is in consistent with our work.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Direct insertion is composed of tendon, unmineralized fibrocartilage, mineralized fibrocartilage, and bone, while indirect insertion anchors the ligament to periosteum by Sharpey's fibers. 11 Li et al 29 and Ai et al 11 have reported IF between the graft and the host bone matured with narrowed width, fibrocartilage formation, and Sharpey's fiber formation at 12 weeks after ACL reconstruction, which is in consistent with our work.…”
Section: Discussionsupporting
confidence: 91%
“…5 Synthetic materials for ACL reconstruction and modification of those materials have been investigated for their potential to address the challenges of osseointegration. [6][7][8][9] Our previous studies have applied gelatin, 10 silk fibroin, 11 and material based on calcium phosphate 12 to artificial ligament using different surface modification techniques, which have shown positive effect on the biological performance. Among these materials, HA has been proved to improve osseointegration after applied on PET ligament.…”
Section: Introductionmentioning
confidence: 99%
“…An in vivo study showed that compared to HA-coated Ti, plasma-sprayed MgO and SiO 2 binary-doped HA-coated Ti implants could significantly enhance bone mineralization and could reach the maximum implant pushout force at week 14 13. Similarly, another study of ultrahigh-molecular-weight polyethylene coated with vascular endothelial growth factor (VEGF)-loaded silk fibroin showed an improvement in the graft-bone healing process in rabbit ACLR models 14. Therefore, the addition of bioactive molecules could further improve the osteointegration of plasma-sprayed HA coatings.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of biology and materials science, biomaterials are developing at an astonishing rate. Nanotechnology (Qian et al, 2017; Huang et al, 2018; Li et al., 2016a; Li et al., 2016b), surface modification technology (Chen et al, 2018; Ren et al, 2015; Ai et al, 2017; Wang et al, 2017), 3D printing (Kelly et al, 2018; Zhu et al, 2016), stem cell technology (Gaffney, Wrona & Freytes, 2018; Merceron et al., 2008) and other leading-edge technologies are accelerating the innovation of biomaterials (Dalby et al, 2004; Li et al., 2016a; Li et al., 2016b; Zhang et al, 2018). The government of China has been increased the investment in research and development, and continued to issue the policies to provide guidance for the development of biomaterials.…”
Section: Introductionmentioning
confidence: 99%